Optimal cytoreductive surgery in patients with disseminated ovarian cancer (the department’s experience) - N. G. Kormosh; K. P. Laktionov; A. N. Gritsai; N. S. Kerzhkovskaya (Опухоли женской репродуктивной системы, 2014)
One hundred and one patients with disseminated ovarian cancer (OC) treated at Surgery Department Eight, Research Institute of Clinical Oncology, N.N. Blokhin Russian Cancer Research Center, Russian Academy of Medical Sciences, in 1998–2007 and continued to be followed up and treated till March 2012 were examined to make a clinical analysis of the course of the disease. Median follow-up was 32 months. The proportion of patients with Stages III–IV OC was 87 %. Optimal cytoreductive surgery was shown to be possible in 21 (20.8 %) patients dur- ing Stage 1 combination therapy and in 20 (19.8 %) patients after neoadjuvant chemotherapy (CT). The maximum survival rates (with a median of 87.7 months) were achieved in 21 patients who had undergone optimal surgery and had a tumor that is highly susceptible to CT with platinum derivatives. It is concluded that it is necessary to improve the diagnosis of the disease for increasing treatment results.